2020
DOI: 10.3390/w12123315
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Excess in Precipitation Reveals Water Vapor Source in the Monsoon Margin Sites in Northwest China

Abstract: The deuterium excess (d) in precipitation, determined by the stable hydrogen and oxygen isotopes (δ2H and δ18O), is a widely applied parameter in tracing the water vapor source. Based on the multiple-year observations of stable water isotopes in precipitation at four stations in the Lanzhou city, Northwest China, we analyzed the variations in deuterium excess in precipitation at the Asian monsoon margin region. The mean value of deuterium excess at the study region is 11.0‰ in the dry season and 8.0‰ in the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Li et al [57] tracked the water vapor sources of Urumqi, Zhangye, and Hetian in the arid region of northwest China using HYSPLIT4.9 and identified that there were two moisture sources in the whole year, namely, the Atlantic water vapor in the westerly belt and the polar Arctic water vapor. At the same time, Chen et al [22] found that the water vapor in the westerly belt played a dominant role in the precipitation of Lanzhou, while the water vapor in the southeast monsoon had limitations and was mainly concentrated in summer. In order to verify the source of water vapor in study area, the reanalysis data during the sampling period (April 2019 to April 2020) were selected to trace the trajectories of 10 days in different seasons and clustered in different directions.…”
Section: Backward Trajectory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [57] tracked the water vapor sources of Urumqi, Zhangye, and Hetian in the arid region of northwest China using HYSPLIT4.9 and identified that there were two moisture sources in the whole year, namely, the Atlantic water vapor in the westerly belt and the polar Arctic water vapor. At the same time, Chen et al [22] found that the water vapor in the westerly belt played a dominant role in the precipitation of Lanzhou, while the water vapor in the southeast monsoon had limitations and was mainly concentrated in summer. In order to verify the source of water vapor in study area, the reanalysis data during the sampling period (April 2019 to April 2020) were selected to trace the trajectories of 10 days in different seasons and clustered in different directions.…”
Section: Backward Trajectory Analysismentioning
confidence: 99%
“…D-excess in precipitation has been reported in conditions in which moisture recycling through evaporation plays a role in indicating the source of water vapor and the hydrological system [18,19]. Many scholars have confirmed that monsoon water vapor has an influence in the northwest region on a large scale to a certain extent [20][21][22]. However, research on the sources of water vapor in the northwestern inland of China found that the water vapor fractionation of precipitation is mainly dynamic and that the raindrops experienced a certain below-cloud secondary evaporation during the falling process, which also mixed with a certain amount of local moisture [23].…”
Section: Introductionmentioning
confidence: 99%
“…Because condensation tends to occur much closer to equilibrium conditions than evaporation, d-excess is often considered a tracer of moisture source changes (e.g. Johnsen et al 1989, Ciais et al 1995, Pfahl and Sodemann 2013, Chen et al 2020. Recently, new logarithmic definitions of d-excess have become popular, because they reduce the d-excess dependence on temperature, making the parameter a better pseudo-conserved tracer of moisture origin during transport (Kopec et al 2016, Dütsch et al 2019.…”
Section: Understanding Oxygen and Hydrogen Isotopes And Fractionationmentioning
confidence: 99%
“…The Fen River headwater catchment is supplied by a series of alpine lakes from the Quaternary remnant of the glaciations [45], and the vegetation coverage in this area is high, with a canopy density of 0.8 [46]. Therefore, water evaporation pools, including evaporation from open water bodies and soil water, and plant transpiration pools, act as secondary moisture sources [47,48]. This is supported by the evidence that the d-excess value decreases to a minimum of 2.41‰ (July 19) after 15 consecutive rain days in the monsoon season (Fig.…”
Section: High D-excess Values In Precipitation Caused By Secondary Ev...mentioning
confidence: 99%